Best Answer

Yes you can answer it!

--

Step 1.

2x(6)=4

Step 2.

2x=4/6

Step 3.

2x=0.6 (repeating)

Step 4.

x=0.6 (repeating)/ 2

Step 5.

x=0.3 (repeating)

More answers

I will help....

You have to solve for x

1) simplify 2x-6=4

2) 2x=?

2) x=?

Hint make 6 equal zero on the left side of the equation

Q: Can you solve 2x 6 equals 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Solution: 2x + 6 = 2 2x = -4 x = -2 Check: LHS = 2*(-2) + 6 = -4 + 6 = 2 = RHS

3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x

Yes and it works out that x = 3 and y = 4

2x-y = 4 and 2y = 4x-6 pick either equation and solve for one of the variables the first equation: y = -4 + 2x plug in the value of variable you solved for into the other equation 2(-4 + 2x) = 4x -6 then solve -8 + 2x = 4x-6 -2 = 2x x= -1 then plug in the value you have found into either original equation to find the value of the other variable 2(-1) - y = 4 -2 - y = 4 -y = 6 y = -6

3x+5=4-2x+6 5x=4-1 5x=3 x=3/5

Related questions

2x - 4 = -10 2x = -10 +4 2x = -6 x = -3

-4

3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6

6 - 3x = 4 - 2x 6 = x + 4 x = 2 Check it. 6 - 6 = 4 - 4 It checks.

Solution: 2x + 6 = 2 2x = -4 x = -2 Check: LHS = 2*(-2) + 6 = -4 + 6 = 2 = RHS

3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x

4x=-10 x=-2.5

Yes and it works out that x = 3 and y = 4

2x-y = 4 and 2y = 4x-6 pick either equation and solve for one of the variables the first equation: y = -4 + 2x plug in the value of variable you solved for into the other equation 2(-4 + 2x) = 4x -6 then solve -8 + 2x = 4x-6 -2 = 2x x= -1 then plug in the value you have found into either original equation to find the value of the other variable 2(-1) - y = 4 -2 - y = 4 -y = 6 y = -6

3x+5=4-2x+6 5x=4-1 5x=3 x=3/5

4

This is already the equation. Now you just have to solve it. x=5.